Pedagogy in Patha-bhavana School of Tagore’s Santiniketan - Banerjee, Sarmila (JOURNAL OF INDIAN EDUCATION, 2009)
The crankiness of the school environment can be eased linking the school knowlegde with the child’s experience outside it in the community. Children grow in intimate contact with the nature around them. School can enrich and enhance child’s intimacy with the nature by sharpening child’s awareness of his own natural environment. Tagore’s ideas about the education of children realized in his own created Shantinketan. This article takes our readers to patha bhavan, school of Tagore’s Shantiniketan, where innovative ideas like bringing child’s experience into the classes which are without boundaries, plurality of textbooks and material, moving beyond textbooks, etc., found adequate place and till today surprising the other systems of education rigid enough to come out of the irony of boundaries in each and every aspect of education.